A variação do preço do petróleo no período pandêmico e de conflitos geopolíticos - Silva, Carlos Eduardo Vaquis (2023)
The variation of oil in recent geopolitical scenarios, shows in a way solidifies the importance of the commodity globally. The main objective of the work is address and analyze the topic, showing the impact that has already been previously compared to the most recent events. It is proposed, therefore, to present comparisons of their relations at different times and verify the influence of the commodity before the world today, showing for one financial perspective, what are the main drivers of price variation in the pandemic and war period.